Modeling the costs and benefits of capnography monitoring during procedural sedation for gastrointestinal endoscopy - Saunders, Rhodri; Erslon, Mary; Vargo, John (Endoscopy International Open, 2016)
Background and study aims: The addition of capnography to procedural sedation/analgesia (PSA) guidelines has been controversial due to limited evidence of clinical utility in moderate PSA and cost concerns.Patients and methods: A comprehensive model of PSA during gastrointestinal endoscopy was developed to capture adverse events (AEs), guideline interventions, outcomes, and costs. Randomized, controlled trials and large-scale studies were used to inform the model. The model compared outcomes using pulse oximetry alone with pulse oximetry plus capnography. Pulse oximetry was assumed at no cost, whereas capnography cost USD 4,000 per monitor. AE costs were obtained from literature review and Premier database analysis. The model population (n = 8,000) had mean characteristics of age 55.5 years, body mass index 26.2 kg/m2, and 45.3 % male. Results: The addition of capnography resulted in a 27.2 % and 18.0 % reduction in the proportion of patients experiencing an AE during deep and moderate PSA, respectively. Sensitivity analyses demonstrated significant reductions in apnea and desaturation with capnography. The median (95 % credible interval) number needed to treat to avoid any adverse event was 8 (2; 72) for deep and 6 (−59; 92) for moderate. Reduced AEs resulted in cost savings that accounted for the additional upfront purchase cost. Capnography was estimated to reduce the cost per procedure by USD 85 (deep) or USD 35 (moderate).Conclusions: Capnography is estimated to be cost-effective if not cost saving during PSA for gastrointestinal endoscopy. Savings were driven by improved patient safety, suggesting that capnography may have an important role in the safe provision of PSA.